Clinical implications of the IMPROVE-IT trial in the light of current and future lipid-lowering treatment options. (11th February 2016) - Serban, Maria-Corina; Banach, Maciej; Mikhailidis, Dimitri P
ABSTRACT: Introduction : A residual risk of morbidity and mortality from cardiovascular (CV) disease remains despite statin therapy. This situation has generated an interest in finding novel approaches of combining statins with other lipid-lowering agents, or finding new lipid and non-lipid targets, such as triglycerides, high-density lipoprotein cholesterol (HDL-C), non-HDL-C, proprotein convertase subtilisin/kexin type 9 (PCSK9) gene, cholesterol ester transfer protein (CETP), lipoprotein (a), fibrinogen or C-reactive protein.Areas covered : The recent results from the IMProved Reduction of Outcomes: Vytorin Efficacy International Trial (IMPROVE-IT) demonstrated an incremental clinical benefit when ezetimibe, a non-statin agent, was added to simvastatin therapy.Expert opinion : The results from IMPROVE-IT revalidated the concept that low-density lipoprotein cholesterol (LDL-C) levels are a clinically relevant treatment goal. This trial also suggested that further decrease of LDL-C levels (53 vs. 70 mg/dl; 1.4 vs. 1.8 mmol/l) was more beneficial in lowering CV events. This " even lower is even better" evidence for LDL-C levels may influence future guidelines and the use of new drugs. Furthermore, these findings make ezetimibe a more realistic option to treat patients with statin intolerance or those who cannot achieve LDL-C targets with statin monotherapy.